Human Capital Management as a Resource in Achieving Competitive Advantage - Riyanto Wujarso; Saprudin Saprudin; Rina Dameria (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The aim is to provide the conceptual framework for the administration of human capital (MHC) and to show how human capital may be employed to secure the competitive advantage of an organization. Human capital is a concept referring to the extra value provided to organizations by humans. It stresses the necessity for strategic human capital investments through commitment, retention, talent management, and learning and development programs. These studies often mostly depend on an examination of the literature available for their data. Study results stress the relevance of human capital and the strategic measures that contribute to success and competitiveness.